2015
DOI: 10.4028/www.scientific.net/kem.659.164
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Physical and Thermal Conductivity Properties of Cement Paste Containing Nanosilica

Abstract: This research was presented the physical and thermal conductivity properties of cement pastes containing nanosilica by mixing three nanosilica particle sizes of 12, 50 and 150 nm, using nanosilica of 1-5 wt%. The water-cementitious ratio (W/C) was 0.5 for all samples. Thermal property coefficients were tested using a direct measuring instrument with surface probe (ISOMET2114). The influence of nanosilica on the physical properties were compressive strength, bulk density, XRD and SEM respectively. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Previous literature showed that the TC of nanosilica added concrete was reduced by 15% to 59%. The study's findings agreed with the results reported by past researchers [7][8][9][10]. A reduction in the thermal conductivity increases the insulation value of the concrete, causing a decrease in heating and cooling costs if such concrete is used in construction.…”
Section: Icctpp-2022supporting
confidence: 89%
See 1 more Smart Citation
“…Previous literature showed that the TC of nanosilica added concrete was reduced by 15% to 59%. The study's findings agreed with the results reported by past researchers [7][8][9][10]. A reduction in the thermal conductivity increases the insulation value of the concrete, causing a decrease in heating and cooling costs if such concrete is used in construction.…”
Section: Icctpp-2022supporting
confidence: 89%
“…Many researchers studied building materials' thermal properties by adding glass fibers, wool, foam, vermiculite, and silica fume [3][4][5][6]. Limited research work was reported on the thermal properties of nano-silica added cement composites [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the mixture S0 group (without rice straw), the compressive strength tended to increase when the amount of rice husk ash added increased, with 10, 20 and 30% additions resulting in compressive strengths of 5.06, 5.22, and 5.79 MPa, respectively. Because in rice husk ash addition is not a replacement of cement, and the RHA particles are small, they can enter the gaps between the aggregates (sand and lateritic soil) causing compaction, which results in the compressive strength being increased (Jittabut et al 2014). In addition, the positive relationship between curing such as age, high temperature, relative humidity, and the comprehensiveness of the pozzolanic reaction.…”
Section: Effects Of Compressive Strength Unit Weight Water Absorptimentioning
confidence: 99%
“…The unit weight in the mixture with 30% of rice husk ash is more than the 10% of rice husk ash equal to 7.00, 5.10, 4.31 and 6.88%, respectively. This is because small particles of rice husk ash can enter the voids of the soil (Jittabut et al 2014). The pozzolanic reaction resulting in a sticky and compact gel fills more pores inside the block and creates an increasingly dense structure (Hirunmasuwan and Isarangkul 2017) with increased unit weight.…”
Section: Effects Of Compressive Strength Unit Weight Water Absorptimentioning
confidence: 99%